PENGARUH PELATIHAN DAN KOMPETENSI TERHADAP KINERJA KARYAWAN - Saripah, Saripah; Mahyudiansyah, Mahyudiansyah; Norfiana, Lita (Servqual: Jurnal Ilmu Manajemen, 2024)
This research aims to examine the influence of training and competency on employee performance at Trio Motor Banjarmasin which is the object of research, both partial and simultaneous influence. This research is included in quantitative research with descriptive methods. This research uses a saturated sample because the population and research sample consists of 35 employees. The data collection technique uses a questionnaire with a Likert scale of 1-5. The data analysis technique uses multiple linear regression. The research results show that there is a significant influence of training on employee performance. The significant influence of competency on employee performance, as well as the simultaneous significant influence of training and competency on employee performance